Synthesis and fluorescent studies of a low molecular weight rotor for living cancer cell imaging. (July 2020) - Zhu, Shulei; Yu, Xumeng; He, Yang; Ma, Mingliang; Lu, Wei
Abstract: A fluorescent and low molecular weight rotor (9 ) based on 1, 8-napthalimide for living cancer cell imaging was designed and synthesized. The effects of solvent polarity and viscosity on the fluorescence spectra of compound 9 were investigated. Rotor 9 exhibited favorable photophysical properties with a large Stokes shift and induced high viscosity sensitivity in a glycerol-ethanol system with an approximately 10-fold increase in emission intensity. The addition of different concentrations of BSA to compound 9 in PBS elicited an 8-fold increase in fluorescence intensity, suggesting superior environmental sensitivity. Fluorescence lifetime measurements also confirmed these results. Furthermore, compound 9 showed time- and concentration-dependent in vitro cellular uptake behavior in MCF-7 cells and other cancer cell lines. CLSM assay of tumor sections from MCF-7 nude mice also confirmed the possibility of tumor imaging. Graphical abstract: Image 1 Highlights: 9 exhibited high viscous and environmental sensitivity. 9 displayed time- and concentration-dependent cellular uptake behavior. 9 exhibited the possibility of tumor imaging.